2007
DOI: 10.1007/s10484-007-9044-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in EEG Current Sources Induced by Neurofeedback in Learning Disabled Children. An Exploratory Study

Abstract: The objective of this work was to explore Neurofeedback (NFB) effects on EEG current sources in Learning Disabled (LD) children, and to corroborate its beneficial consequences on behavioral and cognitive performance. NFB was given in twenty 30-min sessions to 11 LD children to reduce their abnormally high theta/alpha ratios (Experimental Group). Another five LD children with the same characteristics received a placebo treatment (Control Group). In the Control Group no changes in behavior or EEG current source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 80 publications
(74 reference statements)
2
29
0
3
Order By: Relevance
“…An additional report by Fernandez (Fernandez et al, 2007) on 16 children with learning disabilities documented significant EEG changes 2 months after neurofeedback compared to a placebo-control group where there were no EEG changes, and 10 of 11 children in the neurofeedback treatment group showed objective changes in academic performance compared with one in five children in the placebo group. Other articles have also been published on the value of neurofeedback with learning disabilities (Orlando & Rivera, 2004;Tansey, 1991a;Thornton & Carmody, 2005).…”
Section: Learning and Developmental Disabilitiesmentioning
confidence: 97%
“…An additional report by Fernandez (Fernandez et al, 2007) on 16 children with learning disabilities documented significant EEG changes 2 months after neurofeedback compared to a placebo-control group where there were no EEG changes, and 10 of 11 children in the neurofeedback treatment group showed objective changes in academic performance compared with one in five children in the placebo group. Other articles have also been published on the value of neurofeedback with learning disabilities (Orlando & Rivera, 2004;Tansey, 1991a;Thornton & Carmody, 2005).…”
Section: Learning and Developmental Disabilitiesmentioning
confidence: 97%
“…F. Lubar, Swartwood, Swartwood, & Timmermann, 1995). Brain imaging studies of children with ADHD or LD showed meaningful relations between the behavioral symptoms of these disorders and neurophysiological factors (Castellanos, 1997;Fernandez et al, 2007;Filipek, 1999). Moreover, recent studies of the relationship between electroencephalography (EEG) and ADHD have supported the NFB training protocols (Arns, Gunkelman, Breteler, & Spronk, 2008;Monastra, Lubar, & Linden, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…První studii zjišťující efektivitu metody na děti s poruchami učení publikovali Fernández et al (2003), kontrolované studie provedli Becerra et al (2006) a Fernández et al (2007. Děti absolvovaly terapie na EEG biofeedbacku v rozmezí 20-35 sezení.…”
Section: Eeg Biofeedbackunclassified
“…Co se týče výsledků ohledně změn v mozkových vlnách, bylo by vhodné zahrnout do pretestu a posttestu neurologické vyšetření pomocí kvantitativního EEG, jak je tomu zvykem v rozsáhlejších studiích ověřujících efektivitu EEG biofeedbacku (např. Fernández et al, 2007;Orlando & Rivera, 2004). Bylo by pak možné ověřit statistickou významnost těchto změn.…”
Section: Diskuseunclassified